Sovereignty suspended building the so-called state - Bryant, Rebecca (University of Pennsylvania Press, 2020)
All Cypriots have lived for more than forty years with the political, economic, and psychological consequences of an unresolved conflict and a divided island. Moreover, as citizens of an unrecognized state, Turkish Cypriots' ability to do well or to continue doing well is always improvisatory, as they constantly adapt to whatever limitations are being imposed on their ability to trade, study, and travel. Despite the conflict, citizens of the recognized RoC are able to plan their lives and the lives of their children with the assumption that they will continue to live in a recognized, EU-member state. Citizens of the so-called Turkish Republic of Northern Cyprus, live their daily lives with what they invariably call belirsizlik, uncertainty. That uncertainty arises from not knowing one's place in the world, from not being "seen" or recognized, and from the knowledge that the shape, form, and substance of their so-called state could be significantly altered with a pen stroke --
Keywords: Geschichte 1950-2003; Zyperngriechen; Außenpolitik; Türken; Soziale Situation; Zypern; Nordzypern; Nation-building / Cyprus, Northern; Self-determination, National / Cyprus, Northern; Turks / Cyprus / Social conditions; Cyprus, Northern / Politics and government; Cyprus, Northern / International status; Cyprus, Northern / Foreign relations; Diplomatic relations; International law; Nation-building; Politics and government; Self-determination, National; Turks / Social conditions; Cyprus; Northern Cyprus